Penerapan Sistem Jalan Umum Pintar Berbasis Arduino dengan Supply Tenaga Surya di Desa Banjarwaru - Fadhillah Hazrina; Erna Alimudin; Riyani Prima Dewi; Zaenurrohman Zaenurrohman; Artdhita Fajar Pratiwi; Sugeng Dwi Riyanto; Purwiyanto Purwiyanto (Madani : Indonesian Journal of Civil Society, 2026)
Banjarwaru Village in Cilacap Regency is facing problems related to the lack of Public Street Lighting (PJU), with several vital road sections being dark at nite. This condition significantly reduces safety levels, increases the risk of crime and accidents, and hinders the mobility and socio-economic activities of the community. Residents, especially women and children, feel unsafe to go outside, which impacts religious, social, and economic activities. Responding to this urgency, this community service program aims to improve the quality of life and well-being of the Banjarwaru Village community through the application of appropriate technology. The proposed solution is the installation of two units of an Arduino-based smart street lighting system powered by solar energy. The implementation method for this service involves field observation and experimentation in the design and construction process of public streetlights, and technology transfer to the community. The results of creating a smart public street light based on Arduino with solar power supply function well. At night, electricity is supplied by batteries. The batteries are charged during the day, when the solar cells receive sunlight. The final activity in this series of community service, and the closing event, was the handover and guidance to the Banjarwaru community, thru the Village Head of Banjarwaru, on how the smart public street lighting system powered by solar energy works and how to maintain it.